All-angle unidirectional flat-band acoustic metasurfaces - Chenglin Han; Shida Fan; Hong-Tao Zhou; Kuan He; Yurou Jia; Changyou Li; Hongzhu Li; Xiao-Dong Yang; Li-Qun Chen; Tianzhi Yang; Cheng-Wei Qiu (Nature Communications)
Abstract Flat bands have empowered novel phenomena such as robust canalization with strong localization, high-collimation and low-loss propagation. However, the spatial symmetry protection in photonic or acoustic lattices naturally forces flat bands to manifest in pairs aligned at an inherently specific angle, resulting in a fixed bidirectional canalization. Here, we report an acoustic flat-band metasurface, allowing not only unidirectional canalization at all in-plane angles but also robust tunability in band alignment. The twist, tilt, and skew angles of the bilayer metasurface can be flexibly controlled to break both in-plane and out-of-plane spatial symmetries. These features can thereby turn arbitrary twist angles between bilayers into ‘magic angles’, while maintaining all unidirectional canalization and band alignment tunability. This work may significantly contribute to pushing twisted moiré physics into higher dimensions and facilitate the application of advanced acoustic or optical devices.